Determinants for Quality of Work Life: An explanatory study of Malaysian Generation Y Employees - Wai Yian, Chek; Li-Chen, Lim; Leong-Weng, Lee; Huey Wern, Wong (International Journal of Psychosocial Rehabilitation, 2020)
Objective: The purpose of this study is to examine the effects of job involvement, job satisfaction and job satisfaction on quality of work life among Generation Y employees from selected eight technology companies in Klang Valley, Malaysia. Methodology: A questionnaire survey was administered to 400 employees in eight technology companies in Klang Valley, Malaysia. Descriptive, correlation and regression analysis as statistical tools were used to analyze the data and test the hypotheses that job involvement, job satisfaction and job stress influenced quality of work life. Results: The postulated relationships were found supported by the data. The research found that job involvement and job satisfaction have significant and positive relationship on quality of work life of Generation Y employees who are working in selected technology companies. While job satisfaction is the best predictor of quality of work life among respondents of this study. Implication: This research presents a conceptually yet empirically supported framework to describe the significance of job involvement, job satisfaction and quality of work life relationships in the technology industry. The study is particularly useful for practitioners by identifying advantages of job involvement and job satisfaction among Generation Y employees. This paper gives valuable reference to senior manager to consider the adoption of involvement of employees in planning or any decision-making process in the technology industry in Malaysia.